Peran Mind Mapping dalam Pengembangan Keterampilan Kreativitas Siswa di Sekolah Dasar - Hakim, Auliya Alfatika; Trianita, Mikyal Novi; Prasetya, Andhika Putra (Indo-MathEdu Intellectuals Journal, 2024)
Learning requires a way of delivering material to foster creative thinking in students, the recommended method is the mind mapping method. The mind mapping method focuses on the combination of colors and shapes to arouse students' interest and enthusiasm in learning activities and help students know what they are learning. This study aims to determine the importance of the role of applying the mind mapping method, examine the procedures of the mind mapping method, the benefits of the mind mapping method, and find out the advantages and disadvantages of implementing the mind mapping method. This research is qualitative research with literature study. The method of obtaining data is by analyzing sources and combining from various other reference sources, such as journals, researches, and books conducted by previous researchers. The mind mapping method involves brain performance by arranging branches such as trees. The pattern of this tree can help and provide stimuli at the stage of remembering each thing learned. Mind mapping encourages students to explore their potential and maximize their thinking creativity process